(untitled) (Journal of Education and Development, 2023)
The researchers explored a mixed methods research design through the analysis of a set of interview data. Saldana’s model was utilized to complete the opening coding data and thematic coding data. Three themes were recognized to support the cooperative learning models. These included: a) Knowing by Undergone Events and Contexts, b) Implementation and Action, and c) Opinions and Perceptions, which consisted of a Cooperative Learning Model (CLM). The frequencies of the terms and phrases consisted of the evidence variables. A generalized linear model (GeLM) was utilized to examine the relationship between the three themes and Cooperative Learning Model. The GeLM analysis reported the relationships between the CLM and three themes. This was a new practice to integrate Saldana’s qualitative data analysis and the GeLM into one mixed methods design.